A Constructionist Approach for the Study of Strategy as Social Practice - Alfredo Rodrigues Leite da Silva; Eloisio Moulin de Souza; Alexandre de Pádua Carrieri (BAR: Brazilian Administration Review, 2012)
The goal of this paper is to present an analytical perspective of strategy as social practice in organizations by thearticulation of proposals by Foucault, Certeau and Moscovici on social dynamics. To accomplish its intents itdiscusses the convergences and divergences between social dynamics in Foucault (1972, 1999, 2003a, 2003b),knowledge, power and subjectivities from Moscovici (1961), and Social Representation Theory (SRT) asarticulated with the concept of everyday strategies and tactics by Certeau (1990). The paper presents the microand macro delineations in investigations involving strategy-making practices in organizations over time. Thestudies of strategy as social practices are focused only on the micro-social level of CEO practices inorganizations and don’t consider the involvement of these practices at the macro-social level. Thus, this paperaims at acknowledging the roles played by experimentation and by the researcher’s theoretical position, but alsoat offering the actors an opportunity to present the micro and macro aspects that involve their strategy practicesin a given organization. This way, a dynamic reference is obtained that allows for the comparison of empiricaldata in the analysis of strategy as a social practice.